Molecular detection of Babesia spp. and Rickettsia spp. in coatis (Nasua nasua) and associated ticks from midwestern Brazil - Perles, L. [UNESP]; Barreto, W. T.G.; de Macedo, G. C.; Calchi, A. C. [UNESP]; Bezerra-Santos, M.; Mendoza-Roldan, J. A.; Otranto, D.; Herrera, H. M.; Barros-Battesti, D. M. [UNESP]; Machado, R. Z. [UNESP]; André, M. R. [UNESP] (Springer Nature, 2023)
Procyonids are reservoirs of many zoonotic infectious diseases, including tick-borne pathogens. The role of coatis (Nasua nasua) in the epidemiology of piroplasmids and Rickettsia has not been fully addressed in Brazil. To molecularly study these agents in coatis and associated ticks, animals were sampled in two urban areas in Midwestern Brazil. Blood (n = 163) and tick (n = 248) DNA samples were screened by PCR assays targeting the 18S rRNA and gltA genes of piroplasmids and Rickettsia spp., respectively. Positive samples were further molecularly tested targeting cox-1, cox-3, β-tubulin, cytB, and hsp70 (piroplasmid) and ompA, ompB, and htrA 17-kDa (Rickettsia spp.) genes, sequenced and phylogenetically analyzed. All coatis’ blood samples were negative for piroplasmids, whereas five pools of ticks (2%) were positive for two different sequences of Babesia spp. The first from Amblyomma sculptum nymphs was close (i.e., ≥ 99% nucleotide identity) to a Babesia sp. previously found in capybaras (Hydrochoerus hydrochaeris); the second from Amblyomma dubitatum nymphs and Amblyomma spp. larvae was identical (100% nucleotide identity) to a Babesia sp. detected in opossums (Didelphis albiventris) and associated ticks. Four samples (0.8%) were positive by PCR to two different Rickettsia spp. sequences, being the first from Amblyomma sp. larva identical to Rickettsia belli and the second from A. dubitatum nymph identical to Rickettsia species from Spotted Fever Group (SFG). The detection of piroplasmids and SFG Rickettsia sp. highlights the importance of Amblyomma spp. in the maintenance of tick-borne agents in urban parks where humans and wild and domestic animals are living in sympatry.
Keywords: Amblyomma dubitatum; Amblyomma sculptum; Babesia sp; SFG Rickettsia sp; Tick-borne pathogens; Zoonosis